Rosenthal's Disease (Hemophilia C or factor XI Deficiency) Revealed by Chronic Epistaxis: The First Observation in Sub-Saharan Africa. - Essohana, Padaro; Kueviakoe, Irénée; Yao, Layibo; Agbetiafa, Kossi; Magnang, Hèzouwè; Koffi, Mawussi; Vovor, Ahoefa (Journal of Hematology and Oncology Research, 2019)
Objective Rosenthal's disease (RD) is a rare constitutional hemorrhagic disorder defined by factor XI deficiency. It is clinically characterized by the presence of minimal haemorrhage. We report the first observation of RD in Togo. Observation Mrs. G. A., 45 years old with no particular pathological antecedents, was referred for anemia in a context of chronic epistaxis. It was a spontaneous anterior exteriorization epistaxis often of great abundance, rocking and which evolved episodically. The patient received several transfusions for anemia. The ear-nose-throat examination was normal and a sinus CT scan found only an inflammatory process of the right maxillary sinus. The blood count showed microcytic severe anemia (2,2g/dl). Hemostasis tests showed a prolonged aPTT (57,9 seconds). Clinical examination documented an anemic syndrome with dry skin. Iron deficiency was found. The hemostasis balance confirmed aPTT elongation. Coagulation factors activity showed normal VIII and IX level, but moderate decrease of factor XI (32%). The family survey was not possible (orphan patient). It is recommended the setting under fresh frozen plasma (FFP) in case of a new episode. Follow-up is in progress. Conclusion In the event of any hemorrhagic syndrome, the isolated elongation of the aPTT must lead to a systematic analysis of intrinsic pathway factors
Keywords: Rosenthal’s disease; factor XI; Lome - Togo